Tata Laksana Terkini Dermatitis Atopik Sedang dan Berat: Dari Patogenesis hingga Terobosan Tata Laksana. - Muhammad Alifian Remifta Putra; Vincent Kharisma Wangsaputra; Raya Makarim Penantian (Cermin Dunia Kedokteran, 2024)
Atopic dermatitis (AD), characterized by recurrent eczematous lesions and pruritus, is a major contributor to the total global burden of disability. The common management practice includes patient education and topical emollients and is heavily reliant on the use of anti-inflammatory agents with systemic corticosteroids. Monoclonal antibodies provide a novel, targeted approach towards specific cytokines. This study aims to highlight the novel systemic therapeutic drug aimed at specific targets. A comprehensive literature review utilizes databases including EMBASE, EBSCOhost, PubMed, Scopus, and Wiley Online Library, using keywords: “monoclonal antibody” AND “therapy” AND “atopic dermatitis”. Relevant papers containing different updates in atopic dermatitis management and the utilization of monoclonal antibodies are included in this review. The current regimen of monoclonal antibodies offers better management of moderate-to-severe AD. Monoclonal antibodies have become a promising therapy as they demonstrate better therapeutic effects in terms of skin barrier protection and anti-inflammatory and pruritusreducing effects. However, its application still faces various challenges such as side effects and infections. The heterogeneity and relapsing nature also add to the complexity and risk profile of AD management.